Imagined Spaces Through Public Space Typography: Preliminary Studies Using Multimodal Ethnography - Putra, Wibisono Tegar Guna; Apsari, Diani (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
Text cannot be separated from its context, nor can the complexity of reality be reduced. The relationship of the text as a visual element between the imagined spaces that follow is what this study tries to explain further. In this article, the authors choose the quote,